Waiting Time of Patients in Outpatient Hospital Before and After Pandemic Covid 19: A Literature Review - Fitra Pringgayuda; Faridah Hashim; Nahla Abduljaleel Yahya Alsaidi (State Islamic University of Sunan Ampel, 2022)
Patient waiting times is an important factor that affecting hospital services quality. Waiting time will affect service satisfaction and repeat visits at the hospital, especially for outpatients. This study aims to determine the literature review of the patient waiting time at the hospital. Method: The literature review method with the PRISMA approach used in this literature review. Synthesis of data used the PICO method. The articles source was through Google Scholar, Pubmed NCBI and DOAJ. The inclusion criteria set were articles with the keywords